Making Feminist Media. - Groeneveld, Elizabeth (Film + media studies., 2015)
"It's about the media and craft cultures generated by Riot Grrrl and feminism's third wave. Its focus is on the feminist publications that began as zines in 1990s; in tracing their history, the author provides insight into the politics of feminism's recent past."--